PERBEDAAN TINGKAT ADAPTABILITAS KARIER SISWA SMK BOARDING SCHOOL DITINJAU DARI JENIS KELAMIN - Chairunnisa, Vania Alvicka; Dasalinda, Dwi (Jurnal Ilmiah Global Education, 2023)
SMK students are designed to prepare the nation's generation so that after graduating students are better prepared to work and more easily get jobs in accordance with their respective expertise competencies. However, the fact is that in one vocational school with a boarding school system, many female students do not work immediately, unlike male students. Career adaptability is a psychosocial construct that shows that an individual has the readiness and ability to face current or future career development tasks, face educational or work transitions, and face the difficulties and risks experienced. This study aims to determine whether there are differences in the level of career adaptability of vocational boarding school students in terms of gender. The research was conducted at one of the boarding school SMKs in Jonggol. The subjects in this study were 104 students including women and men. Data collection uses a hardiness scale containing 24 Career Adapt-Abilities Scale (CAAS) items. The sampling technique used saturated samples for women and proportional stratified random sampling for men. Data analysis was carried out with the statistical technique of independent sample t-test with the help of SPSS 26.0 for Windows program. The results of data analysis showed that there was no difference in the level of career adaptability of vocational boarding school students in terms of gender (sig> 0.05).